Multicultural Counseling Approach in Addressing Diversity in Schools - Wahyuni, Nur (PT. Anagata Sembagi Education, 2025)
Indonesia as a multicultural country faces serious challenges in managing diversity in the educational environment. Multicultural counseling is a key strategy to build cultural awareness, inclusivity, and student character. This study aims to analyze the effectiveness of multicultural counseling in increasing cultural awareness, strengthening inclusivity, and supporting student character formation through systematic literature review. The PRISMA method was used in analyzing 948 articles from the Consensus, Semantic Scholar, PubMed, ERIC, and PsycINFO databases, with 50 relevant articles analyzed in depth. The results of the meta-analysis showed that multicultural counseling had a significant impact on cultural awareness (d = 0.78), inclusivity (d = 0.65), and tolerance (d = 0.71), with key success factors including counselor competence, school systemic support, and program duration. This research confirms the novelty in the form of a comprehensive evidence-based synthesis in the context of Indonesian education, while affirming its global relevance to the SDGs 4 agenda on inclusive education. Thus, multicultural counseling is not only theoretically important but also practical in realizing equitable, equitable, and socially equitable education